В решении.
Объяснение:
3х² + у = 6
4х² - у = 1
Сложить уравнения:
7х² = 7
х² = 1
х = ±√1
х₁ = -1;
х₂ = 1.
у = 6 - 3х²
у₁ = 3;
у₂ = 3.
Решения системы уравнений: (-1; 3); (1; 3).
Відповідь:
Пояснення:
В решении.
Объяснение:
3х² + у = 6
4х² - у = 1
Сложить уравнения:
7х² = 7
х² = 1
х = ±√1
х₁ = -1;
х₂ = 1.
у = 6 - 3х²
у₁ = 3;
у₂ = 3.
Решения системы уравнений: (-1; 3); (1; 3).
Відповідь:
Пояснення:
3х² + у = 6
4х² - у = 1
Сложить уравнения:
7х² = 7
х² = 1
х = ±√1
х₁ = -1;
х₂ = 1.
у = 6 - 3х²
у₁ = 3;
у₂ = 3.
Решения системы уравнений: (-1; 3); (1; 3).